Erra Epic, Tablet IV, 1.49: NABU 1987/69 - Vanstiphout, H. L. J.
"Even on the expanse of the vast sea, with water stretching for a hundred double miles, may they (have to) propel the fishing barge with a punting pole" - zu wenig Wasser unter dem Kiel!